Mecanismos antiulcerogênicos e atividade anti-inflamatória intestinal de combretum duarteanum cambess. (combretaceae) em modelos animais - Morais, Gedson Rodrigues de (2015)
Combretum duarteanum Cambess, is a unique shrub species from South America, and is found in Bolivia, Paraguay, and Brazil, popularly known as mufumbo, cipiúba or cipaúba. It is associated with the caatinga environments, and is popularly used for treat ulcers, inflammation, and infections. Such effects are usually associated with pentacyclic triterpenes. Crude ethanol extract (EEtOH-Cd), and hexane phase (FaHex-Cd) obtained from the leaves of C. duarteanum were evaluated for mechanisms of action involved in its antiulcerogenic and intestinal anti-inflammatory activity in rats. The administration (p.o.) of FaHex-Cd or EEtOH-Cd for 14 days promoted healing of gastric ulcer induced by acetic acid. It has been demonstrated that its effect is related to increases in the total number of cells in the lesion (p<0.05), increasing the number of vessels (p<0.01) and mucus production, and rearrangement of the morphological structures of the gastric tissue. EEtOH-Cd (at 250 mg/kg) or FaHex-Cd (at 250 mg/kg) were evaluated for their antioxidant and cytoprotective effects involved in gastroprotection. Involvement of the antioxidant system with the participation of superoxide dismutase (SOD), catalase, and glutathione (GSH) (p<0.01) in gastric protection against ischemia and reperfusion-induced ulcers was observed. The antiulcerogenic effect of EEtOH-Cd (at 31.25, 62.5, and 125 mg/kg) (p<0.01) or FaHex-Cd (31.25 and 62.5 mg/kg) (p<0.01) was also shown against to the cysteamine induced duodenal ulcers. In models of acute ulcerative colitis induced by trinitrobenzene sulfonic acid (TNBS), EEtOH-Cd or FaHex-Cd were evaluated (at 31.25, 62.5, 125 and 250 mg/kg). EEtOH-Cd (62.5 to 125 mg/kg) or FaHex-Cd (62.5 to 125 mg/kg) caused significant reductions in macroscopic lesion scores (p<0.05) and ulcerative lesion area (p<0.01). This was reflected in reduced rates of diarrhea for animals who received EEtOH-Cd (125 mg/kg) (p<0.01) or FaHex (62.5 mg/kg) (p<0.05). Intestinal anti-inflammatory effect was also evaluated in a relapsed ulcerative colitis model. EEtOH-Cd (125 mg/kg) or FaHex-Cd (62.5 mg/kg) significantly reduced the macroscopic damage (p<0.05, p<0.01, respectively). FaHex-Cd (62.5 mg/kg) was able to significantly reduce the weight/length ratio of the colon (p<0.01), diarrhea (p<0.05), decreased water and food consumption (p<0.01), and consequent weight loss (p<0.05). EEtOH-Cd (125 mg/kg) or FaHex-Cd (62.5 mg/kg) were able to inhibit a increase in myeloperoxidase (MPO) (p<0.01), as well as of proinflammatory cytokines TNF-α (p<0.01), and IL-1β (p<0.01). There was increased anti-inflammatory cytokine IL-10 in animals treated with the tested plant sample (p<0.05). Intestinal anti-inflammatory effect is related to decreased expression of cyclooxygenase-2 (COX-2) (p <0.001), proliferating cell nuclear antigen (PCNA) (p <0.001) and increase in SOD (p <0.001) .Therefore, these data indicate that C. duarteanum has gastroprotective, and intestinal ulcerogenic anti-inflammatory activity. Such effects may involve participation of the antioxidant system and those cytokines principally related to inflammatory bowel disease.